(untitled) (Global Journals of Research in Engineering, 2025)
The aim is demonstrating Earth s outer core liquid metal flow can create geomagnetism itself without having to resort to Geodynamo effect Geomagnetism Generation is currently a mystery and leading existing theory Earth s core and Geodynamo hasn t yet been able to explain Earth s magnetism formation clearly Explore another way Earth s magnetism is formed by electric current movement through the outer core s liquid metal flow considered as a whole and not divided into separate convection currents This leads us to a more straightforward geomagnetism theory without adding a sum of convection currents to create a global magnet that covers the Earth The result is a reasonable theory of geomagnetism that would also explain Magnetic Declination and Geomagnetic Reversal while opening a new way on Sun s magnetism and planets magnetism research